1963
DOI: 10.1017/s0016756800055060
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of Two Intersecting Pre-Cambrian Orogenic Belts in Singhbhum and Adjacent Areas, India

Abstract: Intensive structural and stratigraphic studies, supplemented by nine new absolute age data, have led to the recognition of two distinct orogenic belts in the Pre-Cambrian tract of Singhbhum and adjacent areas in India. The Iron Ore orogeny in the south, characterized by the generally low grade rnetamorphic, N.N.E.-S.S.W. trending formations, had its culmination in the emplacement of the batholithic body of Singhbhum granite (c. 2,000 m.y.). These rocks are separated by a prominent thrust zone (Copper Belt thru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The type area of the IOG (c.3,100 Ma; Saha et al, 1988) lies in the Noamundi‐Jamda‐Koira valley in the southern part of western IOG basin (trending NNE–SSW). Earlier workers suggested a synclinorium structure for the western IOG which was confirmed subsequently on the basis of tectonic analysis endorsing to a regional structure of synclinorium overturned towards the southeast (Jones, 1934; Sarkar & Saha, 1962, 1963). Mukhopadhyay et al (2008) documented 3,506.8 ± 2.3 Ma U–Pb SHRIMP Zircon age for dacitic lava from the southern IOG.…”
Section: Geological Settingmentioning
confidence: 78%
“…The type area of the IOG (c.3,100 Ma; Saha et al, 1988) lies in the Noamundi‐Jamda‐Koira valley in the southern part of western IOG basin (trending NNE–SSW). Earlier workers suggested a synclinorium structure for the western IOG which was confirmed subsequently on the basis of tectonic analysis endorsing to a regional structure of synclinorium overturned towards the southeast (Jones, 1934; Sarkar & Saha, 1962, 1963). Mukhopadhyay et al (2008) documented 3,506.8 ± 2.3 Ma U–Pb SHRIMP Zircon age for dacitic lava from the southern IOG.…”
Section: Geological Settingmentioning
confidence: 78%
“…The SSZ occurs close to the stratigraphic boundary between the Dhanjori Group and the Chaibasa Formation of the Singhbhum Group. The SSZ is interpreted to represent a deep-seated, crustal-scale, N-dipping tectonic dislocation zone (Sarkar & Saha, 1962; Banerji, 1969, 1981), which localized penetrative shear deformation during top-to-south thrust movement of the NSMB block onto the southern Archaean Singhbhum Craton (Ghosh & Sengupta, 1987; Sengupta & Ghosh, 1997; Mukhopadhyay & Matin, 2020; Roy & Matin, 2020). Based on structural observations, such as a continuous increase in the deformation intensity, increasing fold tightness and continuity of mineral lineation from the NSMB to the SSZ, Ghosh & Sengupta (1987) suggested that the progressive deformation in the mobile belt and in the SSZ was synchronous.…”
Section: Geological Settingmentioning
confidence: 99%
“…According to the pioneer workers, the Kuliana gabbro‐anorthosite rocks are coeval with the rocks of the basic volcanics‐dominated Iron Ore Group, and thus older than the Singhbhum Granite (Dunn and Dey, ). On the basis of field relations from some other locations in the eastern Indian shield, Sarkar and Saha (, ) interpreted a younger age of this suite relative to the Singhbhum Granite. Furthermore, in contrast to the view of comagmatic evolution of these gabbro‐anorthosite rocks and the Mayurbhanj Granite, as inferred by Iyenger and Alwar (), a relatively older age of the former has been suggested (Saha et al ., ).…”
Section: Geological Settingmentioning
confidence: 99%